Piracy in the Gulf of Aden : lessons from the Malacca Strait - Ho, Joshua (2009)
Piracy in the Gulf of Aden has reached a level serious enough for the international community to take concerted action. However, the response has largely been more international in nature than regional and national. This contrasts with the measures taken in the Malacca and Singapore Straits in response to the same development.